ANALISIS LITERASI KEUANGAN SYARIAH TENTANG RIBA PADA ANGGOTA BMT/ KOPERASI SYARIAH - Afvan Aquino; Idel Waldelmi; Wita Dwika Listihana (ITB AAS INDONESIA Surakarta, 2022)
The results of the study conclude that the confidence variable of BMT/Sharia Cooperative members shows that the profits obtained by transacting in sharia or doing financing or investing in sharia will get blessings both materially and non-materially in the context of fastabiqul Khairat (competing in goodness) and from other results obtained data that can inform that the skill level of BMT members in conducting every financial transaction in sharia shows the skills to understand very well about transactions in sharia and the knowledge of BMT Islamic members Abdurrab is in the category of strongly agree/very understanding of sharia financial literacy about usury itself. The research was carried out at BMT Islam Abdurab, while the sample was 72 members of the 243 members / population in the study, namely members of the BMT. This research uses descriptive qualitative method.